2002
DOI: 10.1093/jac/dkf079
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic modelling of ciprofloxacin 250 mg/12 h versus 500 mg/24 h for urinary infections

Abstract: A simulation study was performed to evaluate and compare the standard dosage regimen of 250 mg/12 h versus 500 mg/24 h of ciprofloxacin for the treatment of urinary tract infections (UTIs). Pharmacokinetic parameters reported for healthy young and old individuals were used for the simulation of drug levels in urine, at different mean urine flow rates (1-2.5 L/day). Pharmacokinetic/pharmacodynamic analysis of the results revealed that 500 mg ciprofloxacin once a day produced a more favourable profile in urine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…For both azithromycin and ciprofloxacin, serum concentrations in samples collected each day during treatment were consistent with published PK data [33,34]. Of note, plasma concentrations of azithromycin did not exceed the MIC at any time point ( Fig 4B).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…For both azithromycin and ciprofloxacin, serum concentrations in samples collected each day during treatment were consistent with published PK data [33,34]. Of note, plasma concentrations of azithromycin did not exceed the MIC at any time point ( Fig 4B).…”
Section: Resultssupporting
confidence: 88%
“…For each dosing scenario, we simulated the PK profile of azithromycin in plasma and intracellularly (mononuclear cells) in 1,000 patients. The PK profile of ciprofloxacin in systemic plasma was simulated in 1,000 patients for each dosing scenario using the model reported by Sanchez Navarro and colleagues [33] and was again replicated using the simulator tool of Pmetrics.…”
Section: Pharmacokinetic (Pk) Monte-carlo Simulationsmentioning
confidence: 99%
“…This finding demonstrates that short-course therapy with finafloxacin for 5 days for patients with complicated UTIs or acute pyelonephritis was numerically at least comparable to standard 10-day regimens. Likewise, high-dose short courses with levofloxacin (17)(18)(19)(20) and ciprofloxacin in immediate-release (21,22) and extended-release (23-27) formulations, respectively, were equally as effective in the treatment of cUTIs and acute pyelonephritis as 10-day regimens. Furthermore, it has been demonstrated that 7-day ciprofloxacin treatment of female patients with uncomplicated pyelonephritis was as effective as a 14-day course with trimethoprim-sulfamethoxazole (28).…”
Section: Discussionmentioning
confidence: 99%
“…Models with a relative extent of bioavailability (F) for ciprofloxacin given with levofloxacin compared to ciprofloxacin given alone were evaluated. To implement a relative bioavailability, the bolus dose entering the A1 compartment was multiplied by F. Urine flow rate (Flow urine ) was set to 0.058 L/h according to literature data [31,32] and was scaled allometrically with an exponent of 0.75.…”
Section: Methodsmentioning
confidence: 99%